1998
DOI: 10.2214/ajr.171.6.9843315
|View full text |Cite
|
Sign up to set email alerts
|

Normal liver, spleen, and kidney dimensions in neonates, infants, and children: evaluation with sonography.

Abstract: OBJECTIVE. The objectiveof this studywas to determinethe normal rangeof dimen sions for the liver, spleen, and kidney in healthy neonates, infants, and children.SUBJECTS AND METHODS. This prospectivestudyinvolved307 pediatricsubjects (169 girls and 138 boys) with normal physicalor sonographicfindingswho were examined becauseof problems unrelated to the measuredorgans. The subjects were 5 days to 16 years old. All measured organs were sonographically normal. At least two dimensions were ob tamed for each liver,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
224
3
21

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(283 citation statements)
references
References 12 publications
35
224
3
21
Order By: Relevance
“…During the growth duration from infancy to adolescence, development of visseral organs like spleen demonstrated correlation with increases in height, weight and body surface area. Additionally, it was estimated that splenic length measured by ultrasonography provided an objective and safe method to evaluate spleen size (Hosey et al;Megremis et al;Konus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…During the growth duration from infancy to adolescence, development of visseral organs like spleen demonstrated correlation with increases in height, weight and body surface area. Additionally, it was estimated that splenic length measured by ultrasonography provided an objective and safe method to evaluate spleen size (Hosey et al;Megremis et al;Konus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Mean value for men was 14.5 ± 1.6 cm and 13.5 ± 1.7 cm for women. in a study of 307 children aged between 5 days and 16 years, Konus and colleagues 16 , however, found no significant size difference in hepatic lobes.…”
Section: Discussionmentioning
confidence: 89%
“…niederau and colleagues 15 observed that body weight as well as body mass index influence liver size. Konus and colleagues 16 found a correlation coefficient of 0.80 between child's weight and liver size. they found that height is the best parameter for the correlation with longitudinal liver size in the midclavicular line in children (r = 0.85), and concluded that the greater the child's height, the greater the longitudinal extent of the liver.…”
Section: Discussionmentioning
confidence: 97%
“…The longitudinal axis of the spleen was measure at the level of the medial axillary line and the anterior-posterior along the left flank. Reference values for liver and spleen measurements for the different age groups were taken from a study by Konus et al 10 The database was developed and analyzed on Epi-Info version 6.0 public-domain software.…”
Section: Methodsmentioning
confidence: 99%